Infective endocarditis in adult patients with congenital heart disease: results from the ESC EORP EURO-ENDO registry. (14th October 2021) - Van Melle, J; Roos-Hesselink, J; Bansal, M; Kamp, O; Meshaal, M; Pudich, J; Reskovic Luksic, V; Rodriguez-Alvarez, R; Sadeghpour, A; Separovic Hanzevacki, J; Sow, R; Timoteo, A T; et al.
Abstract: Background: Congenital Heart Disease (CHD) predisposes to Infective Endocarditis (IE) Purpose: To characterize and to determine the prognosis of IE in this specific population. Methods: The ESC EORP EURO-ENDO study is a prospective international study in patients (n=3111) diagnosed with IE. In this pre-specified ancillary analysis, we aimed to describe adult patients with CHD (n=365, 11·7%) and compare them with patients without CHD (non-CHD, n=2746) in terms of baseline characteristics and 1-year outcome. Results: CHD patients (73% men, age 44·8±16·6 years) were younger and had less comorbidities. Of the CHD patients, 14% had a dental procedure in the 6 months before hospitalization versus 7% in non-CHD patients (p<0·001) and more often positive blood cultures for Streptococcus viridans (16·4% vs 8·8%, p<0·001). As in non-CHD patients, IE affected most often the left-sided valves. For CHD patients, in-hospital mortality was 9·0% vs 18·1% in non-CHD patients (p<0·001), and also 1-year outcome was more favourable (log-rank for all-cause mortality p<0·0001), even after adjustment for age (Hazard Ratio (HR) 0·61; 95% CI 0·45–0·81). Within the CHD population, multivariable Cox regression revealed the following predictors for mortality: fistula (HR 6·97), cerebral embolus (HR 4·64), renal insufficiency (HR 3·44), Staphylococcus aureus as causative agent (HR 2·06) and failure to undertake surgery when indicated (HR 5·93). Conclusion: CHD patients with IE have better outcome in terms of all-cause mortality. The observed high incidence of dental procedures prior to IE fuels the discussion about the need for antibiotic prophylaxis. FUNDunding Acknowledgement: Type of funding sources: Other. Main funding source(s): Since the start of EORP, the following companies have supported the program: Abbott Vascular Int. (2011–2021), Amgen Cardiovascular (2009–2018), AstraZeneca (2014–2021), Bayer AG (2009–2018), Boehringer Ingelheim (2009–2019), Boston Scientific (2009–2012), The Bristol Myers Squibb and Pfizer Alliance (2011–2019), Daiichi Sankyo Europe GmbH (2011–2020), The Alliance Daiichi Sankyo Europe GmbH and Eli Lilly and Company (2014–2017), Edwards (2016–2019), Gedeon Richter Plc. (2014–2016), Menarini Int. Op. (2009–2012), MSD-Merck & Co. (2011–2014), Novartis Pharma AG (2014–2020), ResMed (2014–2016), Sanofi (2009–2011), Servier (2009–2021), Vifor (2019–2022).